Etiological study of polyclonal hypergammaglobulinemia in a French cohort of hospitalized patients and proposal of a diagnostic aid algorithm - Mallory ANDRE; Anne CONTIS; Annie M. BERARD (Scientific Reports)
Abstract Serum protein electrophoresis can sometimes reveal polyclonal hypergammaglobulinemia. This electrophoretic abnormality can be caused by a variety of conditions and can be difficult to investigate. We sought to investigate screening practices in patients with hypergammaglobulinemia in order to establish diagnostic guidance strategies. We selected all patients with polyclonal hypergammaglobulinemia greater than or equal to 20 g/L over one year to identify the etiologies causing a significant increase in gammaglobulins in the absence of a monoclonal abnormality. We then selected patients who presented with this abnormality for the first time, with no known etiology. Clinical, medication, biological and imaging data were collected. In our study population with polyclonal hypergammaglobulinemia (n = 155), the main etiologies identified were infections (56%), autoimmune and autoinflammatory diseases (20%), liver diseases (18%) and hematological and non-hematological malignancies (6%). Once hypergammaglobulinemia was identified, the clinical examination provided diagnostic orientation but was not sufficient to make the diagnosis. The initial assessment must investigate the most common pathologies including analysis of liver function, viral status, the search for signs of intravascular haemolysis, inflammatory markers, and blood cell count. At the second time point (unless there were suggestive clinical signs at presentation), more specific biological and imaging analyses were required. Finally, we propose a diagnostic guideline for a current, rational and optimal medical practice to assist clinicians in the management of patients with hypergammaglobulinemia.